Critical thinking skills in university students, acquired through research - Cangalaya Sevillano, Luis Miguel (2020)
This research builds upon the notion of critical thinking as espoused by Richard Paul and Linda Elder, who see it as a capability that enables the improvement of one’s own thought, through the acquisition of knowledge, comprehension, and introspection. In this way, critical thinking skills are developed which can be employed by college students: argumentation, analysis, problem-solving, and evaluation. In the case of college students, clearly such skills are indispensable in the development of critical thinking, combined with the support provided by teaching staff, whose role remains essential as a motivating force. Critical thinking in the classroom can be developed through research projects that stimulate students’ reflections, framed by their own context. Such development, founded upon clear criteria, enables the establishing of direct engagement with the skills required for this way of thinking. Therefore, we can conclude that university level research projects enable students to develop the skills and characteristics of the critical thinker.